Exploring and understanding the functional role, and biochemical and structural characteristics of an acidic phospholipase A2, AplTx-I, purified from Agkistrodon piscivorus leucostoma snake venom. (1st March 2017) - Resende, L.M.; Almeida, J.R.; Schezaro-Ramos, R.; Collaço, R.C.O.; Simioni, L.R.; Ramírez, D.; González, W.; Soares, A.M.; Calderon, L.A.; Marangoni, S.; da Silva, S.L.
Abstract: Phospholipases A2 (PLA2 s) constitute a class of extensively studied toxins, isolated from snake venoms. Basic PLA2 isoforms mediate various toxicological effects, while the acidic isoforms generally have higher enzymatic activities, but do not promote evident toxic effects. The functions of these acidic isoforms in snake venoms are still not completely understood and more studies are needed to characterize the biological functions and diversification of acidic toxins in order to justify their abundant presence in these secretions. Recently, Lomonte and collaborators demonstrated, in a proteomic and toxicological study, high concentrations of PLA2 s in the venom of Agkistrodon piscivorus leucostoma. We have, herein, purified and characterized an acidic PLA2 from this snake venom, denominated AplTx-I, in order to better understand its biochemical and structural characteristics, as well as its biological effects. AplTx-I was purified using two chromatographic steps, in association with enzymatic and biological assays. The acidic toxin was found to be one of the most abundant proteins in the venom of A. p. leucostoma; the protein was monomeric with a molecular mass of 13, 885.8 Da, as identified by mass spectrometry ESI-TOF and electrophoresis. The toxin has similar primary and tridimensional structures to those of other acidic PLA2 s, a theoretical and experimental isoelectric point of ≈5.12, and a calcium-dependent enzyme activity of 25.8985 nM/min/mg, with maximum values at 37 °C and pH 8.0. Despite its high enzymatic activity on synthetic substrate, AplTx-I did not induce high or significant myotoxic, coagulant, anticoagulant, edema, neuromuscular toxicity in mouse phrenic nerve-diaphragm preparations or antibacterial activities. Interestingly, AplTx-I triggered a high and selective neuromuscular toxicity in chick biventer cervicis preparations. These findings are relevant to provide a deeper understanding of the pharmacology, role and diversification of acidic phospholipase A2 isoforms in snake venoms. Graphical abstract: Highlights: AplTx-I is an acidic and monomeric phospholipase A2, isolated from Agkistrodon piscivorus leucostoma venom. AplTx-I has high catalytic activity on synthetic and non-micellar substrate. The amino acid sequence of AplTx-I was identified by mass spectrometry. In vitro and in vivo, AplTx-I presented low-level, or lack of, toxicity to mammals and bacteria. AplTx-I promoted an irreversible and selective neuromuscular blockade in biventer cervicis preparations.